Avaliação do teor de potássio no solo e nas plantas em experimento de adubação potássica de longa duração - Sitoe, Elsa Vasco (2024)
The assessment of nutrient content allows for diagnosing soil fertility and the nutritionalstatus of plants, based on crop experiments and chemical analyses of soil and plants. Thelackof adequate evaluation of nutrient content in the soil can lead to various problems, suchasreduced crop production, malnutrition, improper application of chemical fertilizers, andfoodinsecurity. This study aimed to evaluate the potassium content in the soil and plants andtheproductivity of crops. A field experiment was conducted on a sandy dystrophic RedArgisol inan area with a history of potassium fertilization since 1991, at the Soil Department oftheFederal University of Santa Maria-RS. The experiment was conducted in a randomizedblockdesign, in a double factorial arrangement, with potassium doses as the main factors andsplitreapplications as the secondary factor. A spade was used to collect soil samples at depthsof0-10 cm and 10-20 cm, with 3 subsamples taken to form a composite sample in eachsubplot.Soybean sampling was performed using a systematic alternating method along the lengthofalinear meter across five rows for each subplot, allowing for sample collection in areas of2.5m² (1 m x 5 rows x 0.5 m). Biomass sampling of cover crops was collected in eachsubplot inan area of 1 m² using a guide frame as a reference. The potassium content in the soil andplanttissues was analyzed according to Tedesco et al. (1995). The extraction was performedusingMehlich-1, prepared by diluting two strong acids, sulfuric acid and hydrochloric acid, whichare responsible for displacing most of the potassium. The plant tissue samples were subjectedto digestion using nitric acid (HNO3) and perchloric acid (HClO4). The analyses showedadecrease in phosphorus content in the soil in plots with a dose of 180 kg ha -1 of K2Oandadecrease in magnesium content in the leaves with increasing potassiumcontent inthesoil.Grain yield, dry mass, grain size, weight of 100 grains, and potassiumcontent in thesoil andsoybean tissue responded significantly to the potassium levels in the soil. It was possibletoestablish the soil potassium content necessary to achieve 90% of the maximumsoybeanyield,which was 48.8 mg kg -1 , and the production of 90% of the dry matter yield of cover crops,which was 48.9 mg kg -1 .